2001
DOI: 10.1046/j.1439-037x.2001.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Canada Thistle [Cirsium arvense (L.) Scop.] and Faba Bean (Vicia faba L.)

Abstract: This study was conducted to investigate whether density, above‐ground biomass and nitrogen (N) concentration of Cirsium arvense (L.) Scop. cause serious reductions in faba bean (Vicia faba L.) yield. A 2‐year field experiment (1991–93) with four Cirsium densities (0, 4, 16, 64 plants m–2) was carried out. Statistical analysis showed a significant effect of Cirsium density on faba bean yield. Multiple regression analysis showed that the main factors causing faba bean yield losses were the density and above‐grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…Faba bean DM yield losses in our study were greater than those reported by Van Acker et al (1995) in the United Kingdom; they reported autumn‐sown faba bean yields were reduced by 14 to 33% in the presence of 200 barley plants m −2 Our yield reduction was also greater than those reported by Kalburtji and Mamolos (2001) in Greece, where a Canada thistle ( Cirsium arvense L.) density of 16 plants m −2 reduced faba bean biomass by 10%. Differences between the above studies and our findings can be attributed to differences in planting time (autumn versus spring), faba bean cultivar, weed species, weed density, and growing environment.…”
Section: Resultscontrasting
confidence: 68%
“…Faba bean DM yield losses in our study were greater than those reported by Van Acker et al (1995) in the United Kingdom; they reported autumn‐sown faba bean yields were reduced by 14 to 33% in the presence of 200 barley plants m −2 Our yield reduction was also greater than those reported by Kalburtji and Mamolos (2001) in Greece, where a Canada thistle ( Cirsium arvense L.) density of 16 plants m −2 reduced faba bean biomass by 10%. Differences between the above studies and our findings can be attributed to differences in planting time (autumn versus spring), faba bean cultivar, weed species, weed density, and growing environment.…”
Section: Resultscontrasting
confidence: 68%
“…Schepers et al (1992) and Bullock and Anderson (1998) have shown that SPAD readings at high fertilizer N rates demonstrate unique diff erences between plant species. Furthermore, favorable weather conditions are crucial for optimal crop development (Kalburtji and Mamolos 2001), which may correlate directly with SPAD readings, as our fi ndings confi rmed in 2006. It can be concluded that SPAD, RNC, and TNC measured under favorable weather conditions during the growing season may be considered as reliable indicators of crop yield and vice versa; those parameters would not be reliable data for predicting yield in less favorable seasons.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to other winter pulse crops and cereals, the 12 main weeds that compete with faba bean in Europe are the broadleaved species Anthemis arvensis L., Chenopodium album L., Papaver rhoeas L., Sinapis arvensis L., Fumaria officinalis L., Veronica spp., Lamium amplexicaule L., Cirsium arvense (L.) Scop., and the grass species Avena sterilis L., Phalaris spp., Lolium rigidum Gaud., and Alopecurus myosuroides Huds. ( Kalburtji and Mamolos, 2001 ; Karkanis et al, 2016a , b ). Moreover, in many Mediterranean countries, such as Spain, faba bean can be parasitized by various broomrape species ( Orobanche spp.…”
Section: Agronomymentioning
confidence: 99%